Comportamento de oviposição, bioecologia e subsídios para o controle biológico de Stenoma catenifer Walsingham, 1912 (Lepidoptera: Elachistidae) - Nava, Dori Edson (2005)
The goal of this paper was to develop a rearing technique allowing Stenoma catenifer Walsingham, 1912 to be kept in laboratory throughout the year thus providing bioecology, behavior and biological control studies in order to supply subsidies for setting up control strategies within the Pest Management Control precepts. For egg-laying, the avocado seed moth associated chemical (avocado fruit) and physical (paper towel with depressions) stimulation. The oviposition occurred during the scotophase, with 80% concentrating between 8 p.m. and 12 p.m. The avocado seeds were nutritionally more adequate for S. catenifer rearing and the white bean, carrot and yeast-based artificial diet can replace the natural food (seeds). For adults, water or a 10% honey solution was required in the cage for higher longevity and fecundity. Insects reared under artificial diet for seven successive generations kept the same biological characteristics as those insects reared under natural diet. The duration and viability of different biological cycle stages of the avocado seed moth varied according to the temperature, and the viability and fecundity decreased at temperatures of 30 and 32ºC. Male and female longevity was higher at 20ºC in relationship with 25 and 30ºC. The temperature threshold values (Tb) and thermal constant (K) for the biological cycle (egg-adult) were 8.9ºC and 644.5 GD, respectively, varying according to the development stage. Based on the thermal requirements, 7.8 annual generations and 5.1 generations per production cycle were estimated in the region of São Tomás de Aquino, MG. The dynamics of S. catenifer can be an indicator of the number of generations, based on the pests thermal requirements. Five parasitoid species of family Braconidae (Dolichogenidea sp., Hypomicrogaster sp., Apanteles sp., Chelonus sp. and Hymenochaonia sp.) and two of family Ichneumonidae (Eudeleboea sp. and Pristomerus sp.) were found parasitizing S. catenifer, with Dolichogenidea sp. and Apanteles as the most frequent ones. The emergence peak of the parasitoids was observed in the month of August, when a larval parasitism of approximately 30% was observed. The S. catenifer population increased from December through July and towards the harvest a 60% fruit attack was recorded. The highest percentage of attacked fruit had one to four larvae. The losses caused by the borer varied towards the late agricultural season may reach 27%. Bagging of infested fruit was an adequate cultural method to reduce the population of S. catenifer, and the larval mortality in these fruits is proportional to the temperature at the time of bagging. The Trichogrammatoidea annulata De Santis, 1972 and Trichogramma atopovirilia Oatman & Platner, 1983 species/strains were selected in that they parasitized S. catenifer eggs at larger percentages. Under semi-field conditions, the highest parasitism was verified with a ratio of 28 and 30 parasitoids egg, respectively for T. annulata and T. atopovirilia